2014
DOI: 10.1364/oe.22.017508
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a digitized fiber-wireless system employing sigma delta modulation

Abstract: Digitized radio-over-fiber (D-RoF) transport schemes are being pointed as viable alternative solutions to their analog counterparts, in order to avoid distortion/dynamic range problems. Here we propose a novel D-RoF architecture that takes advantage of a bandpass sigma-delta modulator at the transmitter which subsequently permits the usage of a simpler/cheaper base station that avoids the employment of a digital to analog converter. The proposed architecture exploits the properties of the digital signal to ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…5 as a function of driving current. It can be observed that the VCSEL driving current should be sufficiently large to avoid subtreshold operation [6]. On the other hand, gain compression occurs at higher currents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 as a function of driving current. It can be observed that the VCSEL driving current should be sufficiently large to avoid subtreshold operation [6]. On the other hand, gain compression occurs at higher currents.…”
Section: Resultsmentioning
confidence: 99%
“…digital communication with a simple, power efficient RRH while completely eliminating the need for high-speed, high resolution DACs is provided by sigma delta-over-fiber (SDoF) [6], [7], [8] and as shown in Fig. 1c.…”
Section: Introductionmentioning
confidence: 99%
“…where o P is the output of system detected from the PD, i P is the input of system, 1 n , 2 n , and 3 n are the amplitude coefficients ( 2 n and 3 n are coefficients regarding nonlinearities). Clearly, o P is equal to i G ; substituting Eq.…”
Section: Resultsmentioning
confidence: 99%
“…A network which can support both wired and wireless communications concurrently has been necessary because of the increased demands for broad bandwidth and high-speed transmission rate [1][2][3][4]. Delivering hybrid cable television (CATV), millimeter-wave (MMW), and baseband (BB) signals over a lightwave transmission system has many advantages, like broad bandwidth, high-speed transmission rate, and wide service area.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the linearity requirement, different authors [8], [9] explored how low-cost, less linear modulators, such as vertical cavity lasers (VCSELs), can still be used to transmit RF signals. Delta-Sigma modulation of the RF signal oversamples the signal and quantizes the signal to a limited amount of quantization levels (typically 2, resulting in a singlebit stream).…”
Section: Introductionmentioning
confidence: 99%